Acceptability of offering financial incentives to achieve medication adherence in patients with severe mental illness: a focus group study. Issue 8 (27th June 2010) - Priebe, Stefan; Sinclair, Julia; Burton, Alexandra; Marougka, Stamatina; Larsen, John; Firn, Mike; Ashcroft, Richard
Abstract : Background: Offering financial incentives to achieve medication adherence in patients with severe mental illness is controversial. Aims: To explore the views of different stakeholders on the ethical acceptability of the practice. Method: Focus group study consisting of 25 groups with different stakeholders. Results: Eleven themes dominated the discussions and fell into four categories: (1) 'wider concerns', including the value of medication, source of funding, how patients would use the money, and a presumed government agenda behind the idea; (2) 'problems requiring clear policies', comprising of practicalities and assurance that incentives are only one part of a tool kit; (3) 'challenges for research and experience', including effectiveness, the possibility of perverse incentives, and impact on the therapeutic relationship; (4) 'inherent dilemmas' around fairness and potential coercion. Conclusions: The use of financial incentives is likely to raise similar concerns in most stakeholders, only some of which can be addressed by empirical research and clear policies.